From green to blue: a consideration on blue sukuk for the protection of ocean in the Southeast Asia - Mohd. Zain, Nor Razinah; Su, Wai Mon; Ariffin, Noor Azlinah (2022)
Impacted from the aspiration from Sustainable Development Goals (SDGs) as issued by the United Nations, many industries are progressively moving forwards in adapting their businesses and investments to reach such ends. While the economic sustainability is arguably possible to be achieved within the current landscape of Islamic social finance practices, the feasibility of sukuk issuances as a financing mode for project developments is undeniable. By detecting the increase of green sukuk issuances in the global financial market, it is timely to consider the application of blue sukuk for project developments, especially in relation to the protection of ocean in the Southeast Asia. This research focuses (i) to discover the pathway for having blue sukuk issuances in the Southeast Asia, (ii) to investigate the relevant international regulations which need to be considered for project developments relating to ocean; and (iii) to evaluate the sustainable development projects suitable for the protection of ocean in the region. By applying qualitative based research and doctrinal legal approaches, this research traces the latest development from a practical sense as can be observed from the current scenario. As a part of the findings, it is possible to have issuances of blue sukuk as an Islamic social finance instrument for sustainable development projects relating to the protection of ocean in the Southeast Asia. The international regulations are obviously clear on the responsibility of the countries towards protecting the area of the sea that closed to their shores. However, in order to ensure that the blue sukuk issuances for the protection of the ocean and their related sustainable development projects are viable, it is recommended for the countries in the Southeast Asia to consider a strong cooperation through ASEAN.